Study of LDH adaptations associated with the development of Speed endurance in basketball players U19 - Berria, M.; Eddine, S. N.; Adel, B. (International Journal of Applied Exercise Physiology, 2018)
Purpose: The aim of this study was to investigate the effects of 8 weeks regular exercise on (LDH) level enzymes adaptation associated with the specific endurance training program. Methods: Research group consists of total basket players16 males; between 17-18 age range with (0,99±6,27). The participants were divided equally into two groups as Control Group (CG) and Experimental Group (EG). From the beginning of the study to the end of 10-weeks (90min/3day/week) of progressive speed endurance training fitness exercise, the participants were confronted to 2 tests(Test 8*25m,LDH Test) after resting plasma blood samples were done to LDH enzyme test in order to determine the (LDH) levels as biochemical markers. Results: There were no significant difference between pre and post tests in control group, however there were significant difference in (LDH) values in Experimental group between pre and post tests after 10 weeks exercise program (p<0,05). Conclusions: Our findings shows that, 10 weeks of regular speed endurance training application increase the level of (LDH) for basketball players